ACCOMPANY OF PREGNANT WOMEN HIGH RISK THROUGH PREGNANT CLASS IN KARANGMANGU VILLAGE PURWOJATI DISTRCT BANYUMAS REGENCY: PENDAMPINGAN IBU HAMIL RESIKO TINGGI MELALUI KELAS HAMIL DI DESA KARANGMANGU KECAMATAN PURWOJATI KABUPATEN BANYUMAS - linda yanti; Surtinigsih (Jurnal Pengabdian Masyarakat Kesehatan, 2019)
Pregnancy and childbirth are physiological but require good preparation and assistance from family and health professionals to minimize the risk of pregnancy and childbirth complications. From the results of interviews with the Coordinator of Maternal and Child Health at the Purwojati Community Health Center, there were quite a number of problems, including underage or over 35 years of pregnancy, pregnancy outside marriage, pregnancy with Chronic Energy Deficiency (KEK) and anemia in pregnancy. Discomfort of many trimester III pregnancies are also found such as back pain, constipation, frequent urination and swelling in the legs. The purpose of this activity is the formation and activation of classes of pregnant women who are equipped with complementary care and synergize between standard care with innovations that are expected to maximize services at both the Posyandu or Puskesmas levels. Assistance of high risk mothers is carried out with early detection, physical examination, laboratory examination, health education, and also some activities such as pelvic rocking exercise. From the results of early detection conducted in Karangmangu Village, there were cases of pregnant women experiencing chronic energy deficiency of 16.2%, Anemia of 21.1%, pregnancy with diabetes risk of diabetes 8.1%, positive urine protein 5.4% and others pregnancy is accompanied by an infectious disease of 5.4%. In addition to the findings of the problem there are also complaints that are felt by many pregnant women, including constipation, cramps, frequent urination and back pain. The conclusion of this activity is the formation of a class of pregnant women in Karangmangu Posyandu 2 which is implemented in Karangmangu Village Polyclinic so that the pregnant class is not focused in Purwojati Puskesmas, the detection of pregnancy problems so that assistance can be made especially to high risk pregnant women, the increase in knowledge of mothers pregnancy and back pain, cramps, constipation can be minimized with pelvic rocking exercises